STUDY OF LIPOPROTEIN PATTERNS AS AN ATHEROGENIC FACTOR IN T2DM PATIENTS AND THEIR FDRS - Rukh, Gull; Ali, Nasir; Afzal, Naeema; Khan, Taher Salim; Shahjahan, S. (Journal of Ayub Medical College Abbottabad, 2007)
Background: The present study was carried out to determine the lipoprotein patterns as an atherogenic factor in T2DM (Type 2 Diabetes Mellitus) patients and their FDRS (First Degree Relatives). In various previous studies it has been reported that hyperinsulinemia and hyperlipidemia frequently coexist in T2DM patients which indicate that the diabetic state it self is associated with atherogenic lipid disorders. Method: The present study included 26 Type 2DM (T2DM) patients and 21 apparently healthy First Degree Relative (FDRs) of T2DM patients. Twenty three age matched control not related to diabetics were also included in the study. Results: The BMI in male patients and FDRs were significantly higher as compared to controls but no significant difference was seen among the BMI of female FDRs. Fasting plasma glucose (FPG) levels of T2DM patients were significantly higher but no significant difference was observed among the FDRs and controls. FPG did not show any significant correlation with the BMI in diabetic patients, FDRs and controls. The lipid profile of patients showed no significant difference, except the mean LDL-Chol of female patients was significantly higher as compared to female controls. HDL-Chol of males FDRs was significantly lower as compared to male controls. LDL-Chol of female FDRs was significantly lower than the female controls. No significant difference was observed in the total cholesterol and the triglycerides level of the patients of T2DM and FDRs but those cases in which pre-beta band appear upon lipoprotein electrophoresis had significantly higher triglyceride levels as compared to those patients in which pre-beta band did not appear. Conclusion: Lipoproteins of the T2DM patients and FDRs group were found to be highly disturbed as compared to the control group and they show a trend of developing atherogenic states in future. Key Words: Type 2 Diabetes Mellitus (T2DM), First Degree Relatives (FDRs), Body Mass Index (BMI), Lipoproteins, Fasting Plasma Glucose (FPG), Coronary Artery Disease